2012
DOI: 10.1007/s11606-012-2096-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Unintentional Overdose with Non-Prescription Acetaminophen Products

Abstract: BACKGROUND: There is increasing concern over the risk of consumer unintentional misuse of non-prescription (a.k.a. 'over-the-counter') medications containing acetaminophen, which could lead to acute liver failure. OBJECTIVE: To determine the prevalence of potential misuse and overdose of over-the-counter medications containing acetaminophen, either alone or in combination. DESIGN: Cross-sectional, structured interviews with literacy assessment. SETTING: One academic and one community-based general internal med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 24 publications
3
72
0
1
Order By: Relevance
“…Standards or recommendations from organizations like United States Pharmacopeial Convention (USP) are often not implemented until State Boards and/or the FDA adopt them into their regulations. Recent voluntary guidance by the FDA may provide assurances that acetaminophen be spelled out on primary labels, but our research shows this might not be sufficient as a stand-alone strategy to prevent harm to patients [10]. This study demonstrates the importance of the FDA and State Boards of Pharmacy to set a single, clear standard for labeling acetaminophen as an active ingredient and require uniform warnings about concomitant use of acetaminophencontaining products.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Standards or recommendations from organizations like United States Pharmacopeial Convention (USP) are often not implemented until State Boards and/or the FDA adopt them into their regulations. Recent voluntary guidance by the FDA may provide assurances that acetaminophen be spelled out on primary labels, but our research shows this might not be sufficient as a stand-alone strategy to prevent harm to patients [10]. This study demonstrates the importance of the FDA and State Boards of Pharmacy to set a single, clear standard for labeling acetaminophen as an active ingredient and require uniform warnings about concomitant use of acetaminophencontaining products.…”
Section: Discussionmentioning
confidence: 77%
“…Previous investigations, including research by our team, have shown that patients may misinterpret drug labels and cannot recognize acetaminophen as an active ingredient [9,10], which may facilitate unintentional overdoses. The objective of this manuscript is to describe the prescription labeling practices for common acetaminophen-containing analgesics, specifically focusing on how active ingredient information and concomitant use warnings were conveyed.…”
Section: Introductionmentioning
confidence: 96%
“…Studies have found that those who use written sources of information have increased knowledge about the medication, and yet less than half of the consumers can fully understand this information [1]. The worldwide increase over the last 15 years in the use and overuse of OTC medication [2][3][4][5][6][7] has resulted in a critical need to assess the current process of informing OTC medication users of the correct dosage and potential health risks. Specifically, there is a need to identify whether consumers' health literacy can be improved upon, to reduce risks from selfmedicating or medicating children in contradiction to the label instructions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, recent assessments of consumers' decisions about acetaminophen-taking behavior indicate substantial misunderstanding of label instructions relating to exceeding the maximum recommended daily dose and using 1 product containing acetaminophen. 14 On this background, we investigated a revised acetaminophen over-the-counter (OTC) Drug Facts label (ODFL) to determine consumers' use of and preference for a reorganized format with a revised warning heading and inclusion of early signs of liver damage.…”
Section: Introductionmentioning
confidence: 99%